Characteristics of Sonography in a Rat Achilles Tendinopathy Model: Possible Non-invasive Predictors of Biomechanics - Su-Ya Lee (Nature Portfolio, 2017)
Abstract The purpose of this study was to investigate the dynamic changes of histopathology, biomechanical properties, echo intensity, and ultrasound features in a collagenase-induced tendinopathy model of rat Achilles tendons, and to examine the associations among biomechanical properties, echo intensity, and ultrasound features. Forty-two rats received an ultrasound-guided collagenase injection on their left Achilles tendons, and needle puncture on the right ones as the control. At four, eight, and twelve weeks post-injury, the tendons were examined via measurements of their biomechanical properties, histopathological and ultrasonographic characteristics. The injured tendons showed significantly higher histopathological scores, lower Young’s modulus, and higher ultrasound feature scores than the those of control ones throughout the study period. Up to week 12, all injured tendons showed defective healing. The neovascularization score had a significant negative linear association with the failure stress and Young’s modulus. Maximum normalized echo intensity had a significant positive linear association with maximum strain. Therefore, neovascularization and maximum normalized echo intensity are associated with mechanically altered tendinopathic tendons. Non-invasive ultrasound methodology, including echo intensity and ultrasound feature scores, may provide useful information about biomechanical properties of tendinopathic tendons.